Conducting a Correlation Model Between TCM Constitution and Physical Examination Index Based on BPNN Algorithm - Yue Luo; Bing Lin; Chuan-Biao Wen; Mao Luo (KeAi Communications Co., Ltd., 2018)
ABSTRACT: This paper studies the correlation between Traditional Chinese Medicine (TCM) Constitution discrimination and physical examination index based on BPNN algorithm. 253 cases of routine urine test were used to build a linkage model between TCM Constitution and physical indicators via BPNN algorithm. According to the test, the correct rate of learning and test group are 60% and 40%, respectively. A strong correlation was found between TCM Constitution and physical examination indexes. By applying cutting-edge knowledge and technologies, the development and modernization process of TCM can be greatly promoted. Keywords: BPNN algorithm, Constitution of TCM, Physical examination target, Relational model, Preventive treatment of disease